Loss of fiber cell communication may contribute to the development of cataracts of many different etiologies - Beyer, Eric C.; Mathias, Richard T.; Berthoud, Viviana M. (Frontiers in Physiology, 2022)
The lens is an avascular organ that is supported by an internal circulation of water and solutes. This circulation is driven by ion pumps, channels and transporters in epithelial cells and by ion channels in fiber cells and is maintained by fiber-fiber and fiber-epithelial cell communication. Gap junctional intercellular channels formed of connexin46 and connexin50 are critical components of this circulation as demonstrated by studies of connexin null mice and connexin mutant mice. Moreover, connexin mutants are one of the most common causes of autosomal dominant congenital cataracts. However, alterations of the lens circulation and coupling between lens fiber cells are much more prevalent, beyond the connexin mutant lenses. Intercellular coupling and levels of connexins are decreased with aging. Gap junction-mediated intercellular communication decreases in mice expressing mutant forms of several different lens proteins and in some mouse models of lens protein damage. These observations suggest that disruption of ionic homeostasis due to reduction of the lens circulation is a common component of the development of many different types of cataracts. The decrease in the lens circulation often reflects low levels of lens fiber cell connexins and/or functional gap junction channels.